Pengaruh E-servicescape Pada Perceived Value Marketplace Shopee - Sherly Hasna Faradilla; Prabowo, Heri; Sijabat, Rauly (Universitas PGRI Semarang, 2024)
Everything on the Shopee site is of course included in the e-servicescape elements. The e-servicescape on the Shopee site is inseparable from the perceived value or perceived value that arises and will have an impact on customer loyalty. This study aims to analyze the influence of e-servicescape elements on the perceived value of the Shopee marketplace. This research is a type of quantitative research. The population used in this study were students of the PGRI Semarang University Management Study Program, users of the Shopee marketplace site, batch 2019 to 2022. This study took samples using a probability sampling technique, where the selection of population members used the purposive sampling method, the research analysis technique was Structural Equation Modeling (SEM). ) with the help of AMOS 22 software. The results of the up hypothesis show the effect of e-servicescape has a significant positive effect on perceived value